2009
DOI: 10.1177/1073191109349743
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of the Psychopathic Personality Inventory With Offender and Community Samples

Abstract: The Psychopathy Checklist -Revised (PCL-R; Hare, 2003) is a frequently used and well-validated measure of psychopathy, but is relatively time-intensive and expensive to administer. The Psychopathic Personality Inventory (PPI; Lilienfeld & Andrews, 1996) is a self-report measure that provides a less time-intensive and less expensive method for identifying psychopathic individuals. Using three independent samples and two different versions of the PCL (i.e., PCL-R, PCL:SV), we evaluated the extent to which the PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 51 publications
5
72
1
2
Order By: Relevance
“…In line with research on successful psychopaths showing less risky decision making and better executive functions (Ishikawa et al, 2001;Zimak et al, 2014), it can be speculated that improved response inhibition enables psychopathic personalities to obtain short-term goals related to deceitful behaviour, a characteristic which seems to be more pronounced in forensic than subclinical samples since the previous investigation of the PGNG in students did not reveal improvements in response inhibition to be related to psychopathic traits (Weidacker et al, 2017). Whether this dissimilarity to previous research in subclinical samples relates to differences in the construct of psychopathy employed, PPI-R versus PCL:SV, is beyond the scope of this study and should be specifically tested in future studies by using the self-report versions of the PCL-R, such as the Self-report Psychopathy scale, which resembles the factor structure of the PCL-R more closely than the PPI-R (Williams et al, 2007;Malterer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with research on successful psychopaths showing less risky decision making and better executive functions (Ishikawa et al, 2001;Zimak et al, 2014), it can be speculated that improved response inhibition enables psychopathic personalities to obtain short-term goals related to deceitful behaviour, a characteristic which seems to be more pronounced in forensic than subclinical samples since the previous investigation of the PGNG in students did not reveal improvements in response inhibition to be related to psychopathic traits (Weidacker et al, 2017). Whether this dissimilarity to previous research in subclinical samples relates to differences in the construct of psychopathy employed, PPI-R versus PCL:SV, is beyond the scope of this study and should be specifically tested in future studies by using the self-report versions of the PCL-R, such as the Self-report Psychopathy scale, which resembles the factor structure of the PCL-R more closely than the PPI-R (Williams et al, 2007;Malterer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the subclinical sample, participants exhibiting high traits of Blame Externalization, as measured by the Psychopathic Personality Inventory-Revised (PPI-R; Lilienfeld and Widows, 2005), expressed prominent deficits in inhibitory ability when measured with the PGNG (Weidacker et al, 2017). However, research into the relationship between the PPI-R and the PCL has revealed only modest concurrent validity for the total scores of these assessment instruments, and no relationship between the PCL and the Blame Externalization subscale of the PPI-R (Poythress et al, 1998;Benning et al, 2005;Malterer et al, 2010;Miller and Lynam, 2012), and as such it is unclear whether the reported inhibitory deficit in subclinical manifestations of this disorder generalises to a forensic sample. While the full PGNG with its three stage parametric design has not yet been applied to forensic psychopaths, Krakowski et al (2015) utilised a version of the Go/No-go task bearing strong similarities to the lower difficulty level of the PGNG, consisting of an alternation rule to define response inhibition in response to two target stimuli, and reported decreased accuracy on response inhibition trials in psychopathic offenders compared to controls (Krakowski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given the existing extensive research into the PCL-R and related Hare scales, it is not surprising that researchers have begun to compare other measures to the PCL-R, although in some cases such comparisons are highly questionable, for instance the findings of comparisons of the PPI to the PCL-R and PCL-SV (Malterer et al, 2010). The TriPM has been compared to other measures of psychopathy.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…The boldness scale correlates significantly with the interpersonal facet of the PCL-R (argued to be the only facet that captures this element; r= .27) however this correlation was only modest. It has been highlighted that it could be argued that the absence of large correlations is to be expected, given the different measurement domains of a self-report measure and a clinical diagnostic tool such as the PCL-R (Malterer, Lilienfeld, Neumann & Newman, 2010). However, development of the TriPM was also a way to conceptualise psychopathy in a different way to current tools such as the PCL-R. For example, Patrick et al (2009) argue that the PCL-R does not fully capture the boldness element of psychopathy; therefore, it can be argued that correlations with the PCL-R should not be expected to be high as the construct being measured is conceptualised in a different way, and is therefore not the same construct.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Thus, the item-tosubscale relations for the PPI should be worked out. Also of interest would be research that compares the PPI to the PCL-R across diverse samples (Malterer, Lilienfeld, Neumann, & Newman, 2007;Poythress et al, 1998). The PPI was designed to capture psychopathic characteristics suggested by diverse literatures; therefore, it assesses a range of psychopathic trait dimensions.…”
Section: Model Recovery Of Three-factor Efa Via Cfamentioning
confidence: 99%